CNT’s based Nanomaterials: An Interesting Cluster of Biosensors (London Journal of Engineering Research, 2025)
This article outlines the function of carbon nanotubes (CNTs) in the fabrication of biosensors for various applications. We explain why CNTs are employed more frequently in biosensor fabrications for different applications and why CNTs have significant potential in these areas of application by examining the differences between other members of the nano-carbon family. Furthermore, we investigated the role of these nano-carbons in the detection of different analytes in bio-sensing. This chapter focuses on recent breakthroughs in the construction of sensors and biosensors using carbon nanotubes (CNTs). Biosensors are employed in a wide range of applications, from prosthetic devices to checking food quality. Because of the unique physical features of CNTs nanomaterials for biosensing applications, including optical, structural, mechanical, and thermal capabilities, the scientific community has put in a lot of effort.
Keywords: Carbon nanotubes (CNTs); Functionalization of CNTs; Chirality; Arc discharge; laser ablation; Biosensors.